Sex for sale in Scotland : prostitution in Edinburgh and Glasgow, 1900-1939 - Settle, Louise (Edinburgh University Press, 2017)
'Sex for Sale in Scotland' examines the various methods that were used to police female prostitution in Edinburgh and Glasgow between 1900 and 1939, with particular emphasis on the experiences of the women involved.